Prediction of left ventricular remodeling following ST elevation myocardial infarction: role of myocardial deformation parameters. (8th February 2021) - Scarlatescu, AI; Onciul, S; Pascal, A; Petre, I; Zamfir, D; Guzu, C; Iancovici, S; Stoian, M; Vijiiac, A; Onut, R; Dorobantu, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This work was supported by CREDO Project - ID: 49182, financed through the SOP IEC -A2-0.2.2.1-2013-1 cofinanced by the ERDF - I agree that this information can be anonymised and then used for statistical purposes only Background: Left ventricular (LV) remodeling after ST elevation myocardial infarction (STEMI) plays an important role in predicting the outcome of this patient group. It is also useful in assessing the benefit of revascularization. Its identification is also of clinical importance in order to set up preventive strategies for patients with adverse remodeling Purpose: To find an echocardiographic predictor of LV adverse remodeling following STEMI. Materials and methods: In this prospective study we included 52 consecutive patients, aged between 35-70, with STEMI treated by primary PCI. We performed conventional 2D transthoracic echocardiography for patients. In addition to conventional parameters we also measured LV global longitudinal strain (GLS) and LV mechanical dispersion using 2D speckle tracking imaging. For morphological and functional analysis of LV we used 3D echocardiography (volumes, LVEF). LV remodeling (LVR) was defined as an increase of over 15% of the LV end diastolic volume (LVEDV) at 6 months follow up. Results: We found significant differences in time (baseline and 6 month follow up) between LVEF (43, 08 vs 47, 91, p = 0.034), LVEDV (105, 95 vs 113, 21, p = 0.000), LV GLS (-12.61 vs - 14, 58, p = 0.01), and mechanical dispersion (61, 68 vs 56, 11, p = 0.00) in all patients. LV remodeling at 6 months (15% increase in LVEDV) was observed in 30 % of the included patients. At 6 months after STEMI we observed a significant difference between the two groups (remodeling vs no remodeling) regarding 3D LVEF (42.28 %vs 50.30%, p = 0.009), LVEDV (131 ml vs 109 ml, p = 0.05), GLS (-11.15 vs -16.02, p = 0.00) and LV mechanical dispersion (69.02 vs 50.54, p = 0.00). Patients with LV remodeling at 6 months after STEMI had lower LVEF, worse LV GLS and higher LV mechanical dispersion at baseline. Using ROC curve analysis we identified two cut off values, one of -11.55 for baseline LV GLS (Sb 78%, Sp 81%, AUC 0.852, CI 95%, p = 0.00) and another one of 63.7 for LV baseline mechanical dispersion (Sb 71, 4%, Sp 66 %, AUC 0.762, p 0.005) to discriminate between patients with or without LV adverse remodeling at 6 months. Using linear regression analysis, we demonstrated that GLS (p = 0.00) and LV mechanical dispersion (p = 0.016) are able to predict LV remodeling in time. We also found a negative correlation between peak CK-MB levels at baseline LVEF at 6 months. Regression analysis showed that CK-MB levels at baseline could predict LVEF at 6 months (p = 0.008) Conclusion: Baseline LV mechanical dispersion and LV GLS can predict LV adverse remodeling at 6 months after STEMI. These parameters could be used at baseline in order to predict worse outcome in STEMI patients. Further larger scale studies are needed to validate these findings.